Analysis of a castable refractory using the wedge splitting test and cohesive zone model. Issue 13 (October 2019) - Vargas, R.; Neggers, J.; Canto, R.B.; Rodrigues, J.A.; Hild, F.
Abstract: A cohesive zone approach is applied to the wedge splitting test (WST) using the finite element code Abaqus to obtain the tensile strength, the fracture energy and insight about the crack wake region. A finite element model updating (FEMU) method, with a cost function based on the measured load (FEMU-F), is used to calibrate the sought parameters. Digital image correlation (DIC) provided the kinematic boundary conditions, and the images were also used to define the geometry for the finite element analysis. Besides the fracture energy analysis and the experimental load, gray level images and displacement fields are analyzed in order to validate the results. The cohesive region is active in the whole analyzed test as confirmed by estimates using the cohesive length.